Unforgiveness Motivations in Romantic Relationships Experiencing Infidelity: Negative Affect and Anxious Attachment to the Partner as Predictors - Beltrán-Morillas, Ana M.; Valor-Segura, Inmaculada; Expósito, Francisca (Frontiers in Psychology, 2019)
Infidelity is considered an unforgivable betrayal. However, not all behaviours considered unfaithful affect the person who suffers them in the same way. Therefore, to have a better understanding of unforgiveness according to different extradyadic behaviours, two studies were designed. Study 1 (N = 240) explored which extradyadic behaviours are considered as more indicative of infidelity. The results revealed that sexual behaviours were considered more unfaithful when compared with technological, emotional/affective, and solitary behaviours. Study 2 (N = 378) examined the influence of experienced extradyadic behaviours on unforgiveness, negative affect, and anxious attachment to the partner. The results showed that (a) sexual and technological behaviours were less frequently forgiven and promoted a more intense negative affect, (b) anxious attachment was predictive of unforgiveness for sexual and technological behaviours, and (c) negative affect mediated the relationship between anxious attachment and unforgiveness for sexual and technological behaviours. These findings and their possible implications for romantic relationships are discussed.